Circular Composites - Joustra, Jelle; Bessai, Riel (TU Delft OPEN Publishing, 2025)
Composites are increasingly used to optimize the performance of applications as their properties can be tuned to achieve the desired functionality. The sustainability advantages during the use phase are not yet matched by lower impacts in the lifecycle of composite materials and products. In a circular economy this is problematic. This book will serve as a guide to designers who want to contribute with innovative and effective solutions. Circular recovery strategies, ranging from reuse to restructuring and recycling, are connected to the design process and concrete design approaches. By providing clear design guidelines and illustrative examples in a structured way the information is readily accessible and applicable to designers.